Guanxinning Injection Combined With Ischemic Postconditioning Attenuate Myocardial Ischemic Reperfusion Injury in Chronic Renal Failure Rats by Modulating Mitochondrial Dynamics - Anzhu Wang; Anzhu Wang; Dawu Zhang; Dawu Zhang; Jiangang Liu; Jiangang Liu; Huijing Yan; Huijing Yan; Pei Zhang; Pei Zhang; Hui Yuan; Hui Yuan; et al. (Frontiers in Cardiovascular Medicine, 2022)
PurposeSalvia miltiorrhiza Bge. (Danshen, DS) and Ligusticum chuanxiong Hort. (Chuanxiong, CX) have been widely used in traditional Chinese medicine to prevent and treat myocardial ischemia and renal insufficiency, and their extracts (Guanxinning injection, GXN) have been reported to exhibit antioxidant, anti-inflammatory, and anti-ischemia-reperfusion injury properties. It is well-established that ischemic postconditioning (IPOC) can protect against myocardial ischemia-reperfusion (I/R) injury in rats with chronic renal failure (CRF). However, little is known on whether GXN combined with IPOC may affect myocardial I/R injury in CRF rats. We sought to observe the effect of GXN combined with IPOC on myocardial I/R injury in CRF rats by quantifying changes in the expression of proteins related to mitochondrial dynamics.Materials and MethodsIn a survey, 90 Wistar rats were randomly divided into 6 groups (15 rats per group): CRF group, I/R group, comorbid group (CRF + I/R), IPOC group, IPOC + GXN group and the sham group. Changes in blood myocardial injury markers, urea, and creatinine were analyzed. Heart tissues were harvested for histomorphometry and western blotting when rats were sacrificed. Myocardial infarction area was measured by Evans blue and Triphenyltetrazolium chloride solution staining. The expressions of mitochondrial fission relative proteins (DRP1 and FIS1) and mitochondrial fusion relative proteins (OPA1 and MFN1) were detected by western blotting.ResultsIPOC could significantly decrease myocardial injury markers and myocardial area of necrosis (AN)/area at risk (AAR) of the comorbid model rats. Further results showed that GXN combined with IPOC could significantly reduce CK-MB levels and myocardial AN/AAR in comorbid model rats compared with the IPOC group. Meanwhile, both IPOC and IPOC + GXN significantly reduced DRP1 levels and increased the MFN1 and OPA1 protein levels in the comorbid model rats. However, compared with the IPOC group, MFN1 and OPA1 protein levels increased significantly in the IPOC + GXN group.ConclusionExtracts of DS and CX combined with IPOC exert a protective effect against myocardial I/R injury in rats with CRF, mediated by increased expression of mitochondrial fusion proteins (MFN1 and OPA1).